PIEZOSURGERY: A versatile tool in periodontology and oral implantology - Chandra, Bharath; Walavalkar N, Narayan; Praksh, Shobha (International Journal of Dental Research, 2017)
Piezosurgery is a relatively a new technique of bone surgery, that is recently gaining popularity in implantology, periodontics and oral surgery. Piezoelectric ultrasonic vibrations are utilized to perform precise and safe osteotomies. Becauseof its highly selective and accurate nature, with its cutting effect exclusively targeting hard tissue, its use may be extended to more complex oral surgical procedures, as well as to other interdisciplinary problems. It can be used for selective cutting of bone depending on bone mineralization, without damaging the adjacent soft tissue (e.g. vessels, nerves or mucosa), providing a clear visibility in the operating field, and cutting with sensitivity without the generation of heat. So this review discusses the equipment, mechanism of action biological effects on bone, indications, contraindications, advantages and disadvantages of this new technology.